Influence of family and pedagogical communication on school violence (2019)
School violence alludes to peer bullying and aggression in school. The field of communication has studied school violence by analyzing the influence of media and interpersonal relationships on aggressive behaviors. This article provides a perspective on school violence and concentrates on determining the influence of interpersonal communication with parents and teachers on adolescent aggressors and victims in school contexts. A non-experimental correlational-transverse design was used with a sample of 1,082 adolescents (M=15,61; DT=0,90). Three reliable scales were implemented to assess adolescent aggression and parental and pedagogical communication. Findings indicate that aggressions among adolescents at school and the interpersonal communication with parents and teachers present differences associated with gender (p=0,00). At the family level, it was found that offensive communication among parents and children (β=0,225; p=0,00) predicts an increment on school victimization. At the pedagogical level, it revealed that teacher communication intended to discipline students (β=−0,297; p=0,00) and make them see the importance of school and learning (β=−0,120; p=0,04) predicts a decrease in aggressive behavior among adolescents and school victimization. These new findings in education evidence the need to strengthen students’ interpersonal communication with their parents and teachers to obtain better results when implementing strategies to intervene and prevent school violence.